Price volatility, export restrictions and the need for transparency - Illescas, Nelson; Masaro, Jimena Vicentin (International Food Policy Research Institute, 2024)
In this chapter, we explore how the WTO has struggled to fulfill its mission of advancing negotiations post the Uruguay Round. As export restrictions were not prioritized during the creation of GATT and the establishment of the WTO, this led to the utilization of export restrictions by countries, particularly in an unstable context, further exacerbating volatility in agricultural commodities. Moreover, as a result of an insufficient WTO notification system, countries have failed to promptly notify all measures. Furthermore, due to the paralysis of the Dispute Settlement Body, the WTO has lost its enforcement capacity, reducing the incentive for countries to engage in discussions within that forum, even when it is necessary to enhance transparency levels that provide greater certainty to dynamic and stressed markets, which is crucial for driving global food security and ensuring efficient allocation.